Penentuan Harga Pokok Produksi dan Akuntansi Sederhana Bagi Usaha Tambak Ikan dan Sagu Masyarakat - Aaron M.A. Simanjuntak; Cornelia Desiana Matani (The Community Engagement Journal, 2018)
The training of production cost pricing and simple accounting for fish ponds businesses and sago production in community is a community engagement activity that aims to help local entrepreneurs form the village of Yoboi to calculate how much their cost of production and how to construct a simple accounting records for their business.